Adnexal Torsion in Adolescents - Case Series - S, Swetha; S R, Sheela; J Patil, Divya (Journal of Neonatal Surgery, 2025)
BACKGROUND Adnexal torsion, includes torsion of a normal or pathological ovary, torsion of the fallopian tube, Para tubal cyst, or a combination of these conditions, and is fifth most common gynecological emergency. Thirty percent of all cases of adnexal torsion occur in females younger than 20 years. Approximately 5 of 100,000 females aged 1-20 years are affected, with girls older than 10 years at increased risk because of hormonal influences and gonadal growth that result in an increased frequency of physiologic and pathologic masses. The risk of torsion increases when pelvic masses exceed 5 cm 7. The most common ovarian pathologies found in adolescents with adnexal torsion are benign functional ovarian cysts and benign teratomas. METHODS: The study was a retrospective observational study, carried out in the R L Jalappa hospital, kolar. Status of adolescents who presented with pain abdomen and was diagnosed as adnexal mass with torsion, this was studied between J JANUARY 2024 and MARCH 2025 after taking exclusion and inclusion criteria into consideration. Following details were noted which included clinical history, examination, investigations and treatment, ultrasound reports were reviewed and obtained. INCLUSION CRITERIA: All cases of adnexal torsion in adolescents. EXCLUSION CRITERIA: Age more than 18 years RESULTS: CONCLUSION: Adnexal torsion eventually leads to ovarian and possibly fallopian tube infarction; thus, prompt diagnosis is critical to salvage the ovary. A high index of clinical suspicion is required in cases of sudden-onset pelvic pain when it is associated with nausea or vomiting, particularly in premenopausal patients. Therefore, a high index of suspicion coupled with ultrasonographic evidence and adequate clinical presentation reduces morbidity and complications of the disease. Rapid diagnosis and surgical intervention are the keys to recovery